Preparation and Properties of Proton Conductors and HER Electrocatalysts Based on Multifunctional Transition Metal Sulfophosphonates. - Vílchez-Cózar, Álvaro; Salcedo, Inés R.; Xanthopoulos, Konstantinos; Pérez-Colodrero, Rosario Mercedes; Bazaga-García, Montse; Demadis, Konstantinos D.; Olivera-Pastor, Pascual; Cabeza-Díaz, Aurelio (My University, 2025)
Preparation and Properties of Proton Conductors and HER Electrocatalysts Based on Multifunctional Transition Metal Sulfophosphonates Transition metal phosphonates are multifunctional materials with potential applications in energy storage and conversion technologies [1]. These materials exhibit proton-conducting properties and are attractive precursors for the preparation of electrocatalysts [2,3]. Thus, their structurally tunable properties facilitate, on one hand, the formation of efficient proton transport pathways, and on the other, their pyrolytic conversion into electrocatalytically active transition metal phosphides or polyphosphates [4]. Herein, we report the synthesis, structural diversity, and electrochemical characterization of a series of transition metal sulfophosphonates (M = Mn2+, Fe2+, Co2+, Zn2+) derived from 2-[bis(phosphonomethyl)amino]ethanesulfonic acid (SPA). Their crystal structures were determined using synchrotron and laboratory X-ray powder diffraction, allowing structure–property correlations to be established. Depending on the material composition, the proton conductivity values ranged from 10-4 S·cm-1 (Mn2+, Fe2+, and Co2+ derivatives) to 10-2 S·cm-1 (mixed NH4+/Zn2+ derivative) at 80°C and 95% relative humidity, with all compounds exhibiting a water-mediated proton transfer mechanism. In addition, among the transition metal materials pyrolyzed under (5%)H2–Ar atmosphere, the Co-based derivative treated at 700°C, consisting of mixed o-CoP and o-Co2P phases, exhibited the best performance in the hydrogen evolution reaction (HER), achieving overpotentials of only 91 and 95 mV at 10 mA·cm-2 under acidic and alkaline conditions, respectively, when supported on a CFP substrate.

References [1] P. Bhanja, J. Na, T. Jing, J. Lin, T. Wakihara, A. Bhaumik, Y. Yamauchi. Chem. Mater. 31 (2019), 5343–5362. [2] S.-S. Bao, G.K.H. Shimizu, L.-M. Zheng. Coord. Chem. Rev. 378 (2019), 577–594. [3] R. Zhang, S.M. El-Refaei, P.A. Russo, N. Pinna. J. Nanopart. Res. 20 (2018), 146. [4] Á. Vílchez-Cózar, R. M. P. Colodrero, M. Bazaga-García, D. Marrero-López, S. M. El-Refaei, P. A. Russo, N. Pinna, P. Olivera-Pastor, A. Cabeza. Appl. Catal. B 337 (2023), 122963.
Keywords: Rayos X - Difracción; Estructura cristalina (Sólidos); Sincrotrones; Catalizadores de metales de transición; X ray diffraction; Metal phosphonates; Proton conductivity; Synchrotron; Electrocatalysts; Metal phosphides; Crystal structure